Risk factors and prevalence of acute kidney injury among intensive care unit patients: a comprehensive study in a tertiary care setting - Salim Moral, M.; Ahmed, Mohammad Shakil; Hassnul Alam, M.; Siddique, Abul Bashar M.; Taher, Abu; Harun-Ur-Rashid, M. (International Journal of Research in Medical Sciences, 2025)
Background: Acute kidney injury (AKI) is a frequent and severe complication among critically ill patients in the intensive care unit (ICU), contributing to increased morbidity, mortality, and extended hospital stays. Identifying risk factors for AKI is crucial for effective prevention and management. Objectives were to determine the prevalence of AKI and identify associated risk factors among ICU patients at Bangabandhu Sheikh Mujib medical university (BSMMU), Dhaka, during a one-year period. Methods: This cross-sectional study included 122 adult ICU patients admitted between December 2022 and November 2023. Patients with chronic kidney disease (CKD) or prior kidney transplantation were excluded. Data were retrospectively collected from medical records, including demographic details, comorbidities, AKI diagnosis based on kidney disease: improving global outcomes (KDIGO) criteria, treatments, and outcomes. Statistical analyses were performed to evaluate significant risk factors. Results: AKI occurred in 60 patients (49.2%). Patients with AKI had a higher mean age (65.4 years) than non-AKI patients (58.6 years, p=0.001). Hypertension was more prevalent in the AKI group (50% vs. 29%, p=0.02), and sepsis was identified in 60% of AKI patients compared to 19.4% of non-AKI patients (p=0.001). The AKI group experienced higher mortality (46.7% vs. 16.1%, p=0.001) and longer ICU stays (14.8 vs. 8.9 days, p=0.001). Conclusions: AKI is highly prevalent among ICU patients, with age, hypertension, and sepsis as significant risk factors. Early detection and tailored interventions are essential to improve outcomes in this high-risk population.